2013
DOI: 10.1371/journal.pone.0054455
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 Overexpression Augments Cell Migration and Metastasis through EGFR Family Proteins in Triple Negative Breast Cancer Cells

Abstract: IntroductionCurrent studies indicate that triple negative breast cancer (TNBC), an aggressive breast cancer subtype, is associated with poor prognosis and an early pattern of metastasis. Emerging evidence suggests that MUC4 mucin is associated with metastasis of various cancers, including breast cancer. However, the functional role of MUC4 remains unclear in breast cancers, especially in TNBCs.MethodIn the present study, we investigated the functional and mechanistic roles of MUC4 in potentiating pathogenic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 58 publications
1
60
0
Order By: Relevance
“…Some studies showed that EGFR was required for PKC activation in other cell types in response to various stimuli [44,45]. Interestingly, instead of being activated by an EGFRdependent mechanism, the inhibition of cyclic mechanical stress-stimulated EGFR by rottlerin or shRNA targeted to PKCδ suggested that PKCδ might be responsible for the initial EGFR activation in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…Some studies showed that EGFR was required for PKC activation in other cell types in response to various stimuli [44,45]. Interestingly, instead of being activated by an EGFRdependent mechanism, the inhibition of cyclic mechanical stress-stimulated EGFR by rottlerin or shRNA targeted to PKCδ suggested that PKCδ might be responsible for the initial EGFR activation in the present study.…”
Section: Discussionmentioning
confidence: 46%
“…A separate study demonstrated that knockdown of MUC4 in breast cancer cells leads to molecular and biochemical alterations that are necessary for EMT, including reduced expression of mesenchymal markers such as vimentin and vitronectin and increased expression of the epithelial marker cytokeratin 18. 40 These data suggest that MUC4 has an important role in EMT, transforming breast cancer cells into a more migratory and aggressive phenotype.…”
Section: Mucinsmentioning
confidence: 88%
“…It was reported that the dysregulation of miR-150-5p performed diverse functions in different types of cancer (Wu et al, 2010;Srivastava et al, 2011;Huang et al, 2013;Cao et al, 2014). Previously, it was reported that the serum exosomal levels of miR-150-5p was significantly higher in primary CRC patients than in healthy controls, and was significantly down-regulated after surgical resection of tumors, suggesting miR-150-5p is a promising biomarkers for non-invasive diagnosis of the disease (Ogata-Kawata et al, 2014). However, it was uncovered in other researchers that CRC tumors had reduced levels of miR-150-5p expression compared with paired non-cancerous tissue, and miR-150-5p was suggested to be considered as a potential biomarker associated with the prognosis in CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increasing evidence also indicate MUC4 is critical for the progression of other malignancies (Ponnusamy et al, 2008;Rachagani et al, 2012;Mukhopadhyay et al, 2013). It is proposed that MUC4 may be regulated at the transcriptional level via the transforming growth factorβand epidermal growth factor pathways among others (Perrais et al, 2001;Andrianifahanana et al, 2005), and at the epigenetic level via DNA methylation and histone modifications (Vincent et al, 2008).…”
Section: Discussionmentioning
confidence: 99%